The Influence of Problem Based e-Modules on Students' Motivation and Learning Outcomes in Acid-Base Material - Mhd Fadhilah; Bajoka Nainggolan (Universitas Negeri Medan, 2024)
The purpose of this study is to ascertain how problem-based online modules affect students' learning results in acid-base chemistry and to determine the correlation of e-modules with motivation and student learning in acid-base materials at SMA Negeri 11 Medan. This research took a sample consisting of 1 group, namely the experimental group in class XI MIPA 6. Tests for normality, homogeneity, hypothesis, and correlation are used in data gathering procedures. After testing, the prerequisite is that the experimental data is normally distributed, for the homogeneous test the experimental class is homogeneous. To test the hypothesis, test is used One Sample T Test, and to test the correlation test is used Product Moment then the data results are obtained for the value hypothesis tcount > ttable, then Ha is accepted and Ho is rejected with the pret-test value in the experimental class, namely X and the post-test value in the experimental class, namely X, correlation test rcount > rtable, then Ha is accepted and Ho is rejected. The findings indicated that learning results were different before and after receiving media therapy in the form of problem-based e-modules. Additionally, the relationship between students' motivation and the chemistry learning results in problem-based e-modules.